2007
DOI: 10.1021/ac0712291
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantitation of Changes in the Platelet Activating Factor Family of Glycerophospholipids over the Course of Neuronal Differentiation by High-Performance Liquid Chromatography Electrospray Ionization Tandem Mass Spectrometry

Abstract: Glycerophospholipids are important structural lipids in membranes with changes associated with progressive neurodegenerative disorders such as Alzheimer disease. Synthesis of the platelet activating factor (PAF) glycerophospholipid subclass is implicated in the control of neuronal differentiation and death. In this article, we combine nanoflow HPLC and mass spectrometry to screen, identify, and quantitate changes in glycerophospholipid subspecies, specifically PAF family members, over the course of neuronal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…C 16 -PAF and C 18 -PAF are the predominant PAF species present in uninjured tissue (39,40) but differentially accumulate over development of or following injury. Recent studies from our laboratory have shown that C 16 -PAF concentrations increase during neuronal differentiation (41), whereas local C 18 -PAF concentrations have only been shown to increase in the injured central nervous system (32). Here, we show that both C 16 -PAF and C 18 -PAF trigger neuronal death in PAFR-negative cells, but through isoform-specific apoptotic or neurodegenerative signaling pathways, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…C 16 -PAF and C 18 -PAF are the predominant PAF species present in uninjured tissue (39,40) but differentially accumulate over development of or following injury. Recent studies from our laboratory have shown that C 16 -PAF concentrations increase during neuronal differentiation (41), whereas local C 18 -PAF concentrations have only been shown to increase in the injured central nervous system (32). Here, we show that both C 16 -PAF and C 18 -PAF trigger neuronal death in PAFR-negative cells, but through isoform-specific apoptotic or neurodegenerative signaling pathways, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…However, the determination of the exact position of the double bond and the relative number of the positional isomers poses a major challenge in lipidomics [95], [98]. Other challenges also exist for this field including: 1) the observation that different classes of lipids may significantly affect instrument response of [99]; 2) the different patterns that identical lipid species may show when analyzed by various types of mass spectrometers or by the same mass spectrometer in different experimental modes [100] and 3) the limited availability of internal standards with the exact structure of the lipids of interest [101]. Even with these limitations, it is still clear that targeted lipid analysis of serum will always yield an enormous abundance or metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…1A). PAF isoforms were profiled by high-performance liquid chromatography electrospray ionization mass spectrometry (LC-ESI-MS) (12). Lipids with mass-to-charge ratios (m/z) of 450-600 were analyzed in positive ion mode by MS scan for a protonated molecule at expected m/z followed by precursor ion scan for a diagnostic phosphocholine product ion at m/z 184.…”
Section: Resultsmentioning
confidence: 99%